Facebook addiction and personality - Thipparapu Rajesh (Heliyon, 2020)
This study explored the associations between Facebook addiction and personality factors. A total of 114 participants (age range of participants is 18–30 and males were 68.4% and females were 31.6 %) have participated through an online survey. The results showed that 14.91 % of the participants had reached the critical polythetic cutoff score, and 1.75 % has reached the monothetic cutoff score. The personality traits, such as extraversion, openness to experience, neuroticism, agreeableness, conscientiousness, and narcissism, are not related to Facebook addiction and Facebook intensity. Loneliness was positively related to Facebook addiction, and it significantly predicted Facebook addiction by accounting to 14% of the variation in Facebook addiction. The limitations and suggestions for further research have been discussed.